2008
DOI: 10.1266/ggs.83.423
|View full text |Cite
|
Sign up to set email alerts
|

Shorter telomere length with age in the loggerhead turtle: a new hope for live sea turtle age estimation

Abstract: We verified whether telomere length shortens with age in the loggerhead sea turtle (Caretta caretta) by measuring telomere lengths (relative telomere to single copy gene [T/S] ratios) in whole blood and epidermis from 20 captive individuals with a real-time PCR method. There was no significant correlation between age and relative T/S ratios in blood. Although the correlation between age and relative T/S ratios in epidermis was not significant, older turtles had smaller relative T/S ratios in epidermis. It was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 17 publications
2
21
1
Order By: Relevance
“…Telomere length has been found to be negatively correlated with age in snakes [Bronikowski, 2008], turtles [Hatase et al, 2008], alligators [Scott et al, 2006], birds [Haussmann and Vleck, 2002;Haussmann et al, 2003], humans [Tsuji et al, 2002] and in many other taxa, so as a species that is thought to live for over 100 years [Dawbin, 1982;Castanet et al, 1988] tuatara present a good model for examining telomere length and senescence. Indeed, by comparison with other vertebrates, tuatara appear to have relatively long telomeres [H. Bender pers.…”
Section: Telomeresmentioning
confidence: 99%
“…Telomere length has been found to be negatively correlated with age in snakes [Bronikowski, 2008], turtles [Hatase et al, 2008], alligators [Scott et al, 2006], birds [Haussmann and Vleck, 2002;Haussmann et al, 2003], humans [Tsuji et al, 2002] and in many other taxa, so as a species that is thought to live for over 100 years [Dawbin, 1982;Castanet et al, 1988] tuatara present a good model for examining telomere length and senescence. Indeed, by comparison with other vertebrates, tuatara appear to have relatively long telomeres [H. Bender pers.…”
Section: Telomeresmentioning
confidence: 99%
“…values from both techniques showed no relationship with GLG age suggests that telomere length is not influenced by chronological age in this species. This is not the first study to report a lack of relationship between age and telomere length in a wild animal (Bize et al 2009;Hall et al 2004;Hatase et al 2008;Pauliny et al 2005) and reinforce the taxon-specific nature of these relationships. To summarize, this study has shown that AAR produces results that are similar to counting of GLGs in teeth for harp seals.…”
Section: December 2010mentioning
confidence: 49%
“…Thus, it was anticipated that telomeres could provide a direct method for noninvasive estimation of animal age. However, subsequent work demonstrated that for many species of vertebrates, including reptiles (Hatase et al 2008;Scott et al 2006), birds (Bize et al 2009;Pauliny et al 2006;Salomons et al 2009), and mammals (Frenck et al 1998), telomere length and age exhibit a negative but nonlinear relationship (see Haussmann et al 2003a for a case of telomere elongation with age), making age estimation, particularly for older individuals, problematic. In 2 species of seabirds (Phalacrocorax aristotelis and Diomedea exulans) the greatest rate of telomeric attrition occurred between chick and adult stages (Hall et al 2004).…”
Section: Discussionmentioning
confidence: 99%